Resource Mobilization Strategies and Challenges of Public Elementary Schools in Polangui North District , Division of Albay - Carascal, Christian O. (San Miguel, Iriga City: University of Saint Anthony, 2024)
Resource mobilization strategies and challenges of public elementary schools in polangui north district , division of albay.
Includes bibliographical references.
English
Keywords: Mobilization